The Influence of Beauty Influencers on Purchase Decisions with Customer Engagement and Brand Image as Mediation Variables (Skintific Product Study on Generation Z) - Annisa Jati Utami; Edi Rahmat Taufik; Lutfi Lutfi (Return : Study of Management, Economic and Bussines, 2025)
This study discusses burnout among Generation Z employees who are in the early stages of their careers. The objective of this research is to explore burnout more deeply among early-career Generation Z employees. This is a qualitative study that adopts an interpretive paradigm and a case study approach. The participants in this research are Generation Z employees with work tenure ranging from 0 to 2 years. The data collected were analyzed using open coding, axial coding, and selective coding. The findings of this study reveal several factors contributing to burnout among Generation Z employees, including work organization and job content, interpersonal relationships and leadership, work-life balance and job security, workplace values, health and well-being, personality, and offensive behavior. Additionally, this study identifies social stereotypes as a contributing factor to burnout among Generation Z employees. These factors emphasize that burnout is multifactorial and contextual, particularly within the dynamic yet structurally unstable culture of early-stage startups. If companies are able to establish clearer job descriptions and standard operating procedures (SOPs), provide psychological support and open discussion spaces, create informal activities such as sports or social gatherings to improve work-life balance, and adjust compensation systems to match workload demands, employee performance will increase, ultimately leading to business growth.